Police decision-making with young offenders: Examining barriers to the use of diversion options. Issue 1 (March 2020) - Green, Rachael; Gray, Rebecca M; Bryant, Joanne; Rance, Jake; MacLean, Sarah
Youth justice policies in Australia feature an overall welfare-oriented approach and an emphasis on diverting young people away from the justice system. Nevertheless, some young people, particularly those with complex needs, are incarcerated at a young age and are at greater risk of poor outcomes. This paper explores barriers to the use of diversion options by police through analysis of in-depth interviews with 25 police staff. Consistent with the previous literature, role constraints, workload and lack of specialist knowledge were discussed. This paper explores the interplay of these factors with values, beliefs and expectations about young offenders – many of which were framed by experiences of adversarial encounters with young people and damaged faith in the system to rehabilitate. Naturalistic decision-making scholarship is drawn on to identify the potential role of 'schemas' in police use of discretion and of practical strategies that may support welfare and rehabilitation-oriented police practice with young people.